2021
DOI: 10.1038/s41598-021-96266-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of permeation properties of hydrogen gas in sealing rubbers using thermal desorption analysis gas chromatography

Abstract: Permeation properties of hydrogen gas (H2) into nitrile butadiene rubber (NBR), ethylene propylene diene monomer (EPDM), and fluoroelastomer (FKM) which are the strong candidates for sealing material in H2 energy infrastructures, was quantified using a thermal desorption analysis gas chromatography (TDA GC) and a self-developed diffusion-analysis program. The samples were charged with H2 in a high-pressure chamber for 24 h then decompressed into atmosphere, and the mass of H2 released from the sample was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Nishimura et al also found that the volume of NBR with a carbon black filler exposed to high-pressure hydrogen could be recovered after decompression but the hydrogen was still present inside the material [ 39 ]. For hydrogen desorption from the rubber materials with a carbon black filler, the hydrogen adsorbed to the matrix and to the filler exhibited different desorption behavior, and the hydrogen adsorbed onto the carbon black filler was very slowly desorbed [ 40 ]. Therefore, as shown in Figure 5 , the rapid decrease in the early stage indicates the mechanism by which hydrogen desorbs from the matrix, afterwards, the moderate decrease is attributed to desorption from the fillers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nishimura et al also found that the volume of NBR with a carbon black filler exposed to high-pressure hydrogen could be recovered after decompression but the hydrogen was still present inside the material [ 39 ]. For hydrogen desorption from the rubber materials with a carbon black filler, the hydrogen adsorbed to the matrix and to the filler exhibited different desorption behavior, and the hydrogen adsorbed onto the carbon black filler was very slowly desorbed [ 40 ]. Therefore, as shown in Figure 5 , the rapid decrease in the early stage indicates the mechanism by which hydrogen desorbs from the matrix, afterwards, the moderate decrease is attributed to desorption from the fillers.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with the results of the permeability test. It has been demonstrated that the desorption behavior of hydrogen is closely related to the permeation behavior [ 40 ]. However, the relationship between volume recovery and the permeation behavior is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite the promising advancements, several challenges hinder the practical implementation of sustainable polymers for hydrogen storage. Limited hydrogen uptake capacities, the slow kinetics of hydrogen adsorption/desorption, and the stability under operating conditions are among the key challenges to address [43][44][45][46][47][48]. Furthermore, the cost-effectiveness, scalability, and recyclability of sustainable polymer-based storage systems require optimization to compete with conventional storage technologies.…”
Section: Sustainable Polymers For Hydrogen Storage and A Circular Pol...mentioning
confidence: 99%
“…For example, the sealing devices made of FKM rubber are used for devices of FCVs and HFSs such as hydrogen compressors, which require an excellent resistance for hydrogen gas with high temperature and pressure. Because FKM exhibits excellent thermal and chemical resistance and gas barrier properties and the service temperature range of FKM is from −40 to 225 °C, which is much higher than that of other rubber materials [ 8 ], a few studies have investigated the effect of high-pressure hydrogen gas on the physical and mechanical properties of FKM composites and the long-term durability of FKM O-rings [ 9 , 10 ]. Furthermore, NBR is also widely used for seals and fuel hoses in FCVs and HFSs due to its excellent thermal and oil resistance.…”
Section: Introductionmentioning
confidence: 99%